2019
DOI: 10.3390/photonics6030075
|View full text |Cite
|
Sign up to set email alerts
|

Surface Lattice Resonances in THz Metamaterials

Abstract: Diffraction of light in periodic structures is observed in a variety of systems including atoms, solid state crystals, plasmonic structures, metamaterials, and photonic crystals. In metamaterials, lattice diffraction appears across microwave to optical frequencies due to collective Rayleigh scattering of periodically arranged structures. Light waves diffracted by these periodic structures can be trapped along the metamaterial surface resulting in the excitation of surface lattice resonances, which are mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 100 publications
(149 reference statements)
1
21
0
Order By: Relevance
“…In this article, we experimentally study the coupling of the Fano resonance of an asymmetric split ring resonator (ASRR) to the FOLM of the resonator array. Previous studies have shown enhanced Q factors by coupling a lattice mode to inductive–capacitive (LC) resonances and electromagnetically induced transparency‐type (EIT‐type) resonances. Here, we demonstrate FOLM coupling to a Fano resonance obtained through magnetic coupling and observe both Q factor and FoM enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we experimentally study the coupling of the Fano resonance of an asymmetric split ring resonator (ASRR) to the FOLM of the resonator array. Previous studies have shown enhanced Q factors by coupling a lattice mode to inductive–capacitive (LC) resonances and electromagnetically induced transparency‐type (EIT‐type) resonances. Here, we demonstrate FOLM coupling to a Fano resonance obtained through magnetic coupling and observe both Q factor and FoM enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the resonance can be freely engineered in unit cell design, allowing efficient manipulation of the local phase, amplitude, and polarization on a subwavelength scale, thus controlling the overall spectral response and wavefront of the devices. Typical THz metasurface devices include filters, 13,14 sensors, [15][16][17][18] absorbers, [19][20][21] modulators, [22][23][24][25][26] polarization controllers, 27,28 flat lenses, [29][30][31][32] special beam generators, 33,34 holograms, 29,[35][36][37] cloaks, 38,39 etc. Though much more compact than their traditional counterparts, these metadevices have little effect in reducing the size of the THz propagation path in the systems.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the trapped fields, lattice mode behaves as a dark mode existing in the metamaterials and its resonance frequency can be tuned by altering the periodic of meta‐atoms. [ 47–54 ] The lattice modes are observed as kinks or discontinuities in the transmission or reflection spectra of the metamaterials, and also referred to as diffractive modes or Woods anomalies. [ 47–54 ] The frequencies of the lattice modes for a square metamaterial structure can be evaluated as [ 48,52 ] fLM=cnPi2+j2where c is the speed of light in vacuum, n is the refractive index of the substrate, P is the lattice period, and ( i , j ) are non‐negative integers defining the order of the lattice mode.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] However, the toroidal resonance being the lower‐frequency spilt mode implies that coupling to the lattice mode requires a large period to fit the FOLM frequency, which would reduce the efficiency of devices. [ 47–54 ] To settle down this problem, we convert the gap‐coupling (capacitive‐coupling) to side‐coupling (inductive‐coupling) by flipping the arms of the two joint metallic loops, as shown in the inset of Figure 1a. The nature of toroidal resonance is generally identified by analyzing the opposite surface currents oscillating in the two loops.…”
Section: Resultsmentioning
confidence: 99%